Factors Motivating Use of Digital Libraries - McMartin, Flora; Manduca, Cathy; Iverson, Ellen; Wolf, Alan; Morgan, Glenda (the Association for Computing Machinery, 2006)
Knowledge about how users use digital libraries and their contents is inextricably tied to a library's ability to sustain itself, grow its services and meet the needs of its users. This paper reports on the preliminary results of a study of how science, technology, engineering and mathematics (STEM) instructors perceive and use digital libraries. Preliminary findings indicate that: they do not differentiate between digital libraries and other kinds of content that comes from the web, they seek content to supplement traditional teaching methods and their reliance on Google and personal networks impedes their ability to recall the primary sources of useful content.
(c) ACM, 2006. This is the author's version of the work. It is posted here by permission of ACM for your personal use. Not for redistribution. The definitive version was published in Proceedings of the 6th ACM/IEEE-CS joint conference on Digital libraries, {, ISBN:1-59593-354-9, (2006)} http://doi.acm.org/10.1145/1141753.1141808
Keywords: user study; evaluation; digital library; digital learning materials